Comics and the senses : a multisensory approach to comics and graphic novels - Hague, Ian (Routledge research in cultural and media studies, 2014)
Attempts to define what comics are and explain how they work have not always been successful because they are premised upon the idea that comic strips, comic books and graphic novels are inherently and almost exclusively visual. This book challenges that premise, and asserts that comics is not just a visual medium. The book outlines the multisensory aspects of comics: the visual, audible, tactile, olfactory and gustatory elements of the medium. It rejects a synaesthetic approach (by which all the senses are engaged through visual stimuli) and instead argues for a truly multisensory model by wh